The Influence of Timeliness and E - Servqual On Customer Satisfaction With The Delivery Service PT Jalur Nugraha Ekakurir (JNE) Express (Case Study Of JNE Express Mindi Customers In North Jakarta) - Putri Anggraini; Ai Netty Sumidartiny (JAMBIS : Jurnal Administrasi Bisnis, 2021)
This study aims to determine and analyze the effect of timeliness and e-servqual on customersatisfaction with the delivery service of PT Lintas Nugraha Ekakurir (JNE) Express. The dataused was primary data which was collected through the distribution of questionnaires with aLikert scale. The population in this study was 1,844,462 residents of North Jakarta. Withaccidental sampling technique, a sample of 100 respondents was obtained from the population.This study used a quantitative approach. Calculations and data analysis were performed usingSPSS 28.0. The results showed that partially (t test) Punctuality (X1) has a significant effect onCustomer Satisfaction (Y) as evidenced by tcount > ttable (4.234 > 1.984) and the coefficient ofdetermination (r2) of 43.5%. Partially (t test) E-Servqual (X2) has a significant effect onCustomer Satisfaction (Y) as evidenced by tcount > ttable (8.743 > 1.984) and the coefficient ofdetermination (r2) of 62.6%. Simultaneously (f test) Punctuality (X1) and E-Servqual (X2) havea significant effect on Customer Satisfaction (Y) as evidenced by fcount > ftable (104.963 > 3.09)and the coefficient of determination (r2) of 68.4%.